Research on fault lateral sealing of thinly interbedded sandstone and mudstone strata based on the fine calculation method of the SGR value - Liu, Xiaowen; Zhao, Yuwu; Pan, Guohui; Bian, Burong; Song, Xianqiang; Liu, Zongbao; Yu, Jie (Frontiers in Earth Science, 2024)
Terrestrial sedimentary basins are influenced by rapid changes in the clay content, resulting in significant differences in the lateral sealing capacity (shale gouge ratio, SGR) of different parts of the fault. In the present study, we used a method of setting virtual wells and using seismic inversion data to accurately calculate the SGR of faults in strata composed of interbedded sandstone and mudstone calculate the clay content of the strata and to compensate for the low level of the actual well control. Optimal well spacing was determined based on the variable clay content of the formation. The planar variation of the fault throw was characterized via seismic interpretation. We also examined the lateral sealing of faults. The Putaohua oil layer in the S14 area of the Sanzhao Sag in the Songliao Basin was chosen as an case study. Based on the calculation of fault SGR values and the oil distribution, the evaluation criteria for the fault sealing capacity were determined, and the changes in the lateral sealing capacity of the faults were analyzed. This approach accurately estimates fault SGR values and predicts the effective oil-bearing area within the fault zone. It is also suitable for evaluating the lateral sealing of faults in strata composed of interbedded sandstone and mudstone. Our findings provide an in-depth understanding of the lateral sealing of faults and can aid in further research on petroleum distribution patterns.